A Fluorescent and Colorimetric Chemosensor for Hg2+ Based on Rhodamine 6G With a Two-Step Reaction Mechanism - Bai, Cui-Bing; Wang, Wei-Gang; Zhang, Jie; Wang, Chang; Qiao, Rui; Wei, Biao; Zhang, Lin; Chen, Shui-Sheng; Yang, Song (Frontiers in Chemistry, 2020)
A fluorescent and colorimetric chemosensor L based on rhodamine 6G was designed, synthesized, and characterized. Based on a two-step reaction, the chemosensor L effectively recognized Hg2+. The interaction between the chemosensor and Hg2+ was confirmed by ultraviolet–visible spectrophotometry, fluorescence spectroscopy, electrospray ionization–mass spectrometry, Fourier-transform infrared spectroscopy, and frontier molecular orbital calculations. The chemosensor L was also incorporated into test strips and silica gel plates, which demonstrated good selectivity and high sensitivity for Hg2+.